Official Development Assistance (ODA) (Bangladesh Journal of Public Administration, 2021)
It is worthwhile to have a preview of the background of official econonic assistance. In the wake of independence of a large number of former colonies in Asia and Africa, at the end of the second World War and around the time when the Marshal Plan was being implemented in Europe, the former coloilies started to get the attention of their erstwhile colonisers who, in a vast majority of cases, did not want all ties with the periphery sapped all of a sudden. There were political, strategic, commercial and humanitarian consideration for this. The vast new world was viewed in the centres as a potential market for their exports. In addition was the thought of building up zones of influence in these newly independent countries where the way of life would be, given adequate support, on the pattern of the centres. Economic advancement of these countries was viewed as a major factor for sustaining non-inflationary growth in the industrial countries. A sort of interdependence of welfare functions of the peoples living in the two largely disparate worlds was also perceived by many in the industrial countries. There should not be a partage of the world between the very rich and the very poor, many felt obliged to concede. Aid was viewed as 'present day largesse produced by a feeling of post imperial guilt.